Improving sputum culture results for diagnosis of lower respiratory tract by saline washing - (:unkn) unknown (My University, 2010)
Objective: To evaluate the value of Gram staining and bacteriological culture of sputum by the saline wash method for diagnosis of lower respiratory tract infections (LRTI). Methods: All samples containing fewer than 10 squamous epithelial cells per low power microscopic field (10x) were cultured both directly and quantitatively. Results: 620 sputum specimens from 489 patients clinically diagnosed as having LRTI were evaluated. Sensitivity of Gram stain was 78.6% and specificity was 82%, reaching to 100% for H. influenzae and S. pneumoniae. Quantitative method increased overall culture positivity from 52% to 63.5% of inoculated samples. The three most commonly isolated pathogens were Haemophilus influenzae, Pseudomonas aeruginosa and Streptococcus pneumoniae. Conclusion: The collection of expectorated sputum is a non-invasive process and saline washing and subsequent Gram stain and culture can provide a high diagnostic yield. Initial Gram examination of sputum samples, especially for H. influenzae and S. pneumoniae is advisable when experienced microbiologists interpret the slides, since Gram stain is almost as effective as cultivation and the results are available 48 hours sooner.
Keywords: Lower respiratory tract infection; Quantitative culture; Sputum